Establishment and characterisation of Hevea cell suspension cultures - Ziyun W; Hua Y W; Huang H S; Huang T D (Journal of Rubber Research, 2009)
DL 2009
Keywords: Biomass; Cell growth pattern; Plant growth regulator; Suspension cultures